Pengaruh Brand Experience dan Brand Awareness terhadap Kepuasan Pasien yang di Mediasi Kualitas Pelayanan X-Ray Panoramic di Rumah Sakit Brawijaya Saharjo - Dwi Permana Putra; Agus Hadian Rahim; Dadang Kusnadi (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This study aims to analyze the Influence of Brand Experience and Brand Awareness on Patient Satisfaction Mediated by the Quality of Panoramic X-Ray Servives at Brawijaya Saharjo Hospital. The population of this study is 100 people. The sampling technique used is purposive sampling with a sample of 100 people. This type of research is quantitative research. The statistical instrument used is regression analysis using validity, reliability, and normality tests. The results of the research have the influence of brand experience on the quality of Panoramic X-Ray patient service at Brawijaya Saharjo Hospital. There is an influence of brand awareness on the quality of Panoramic X-Ray patient service at Brawijaya Saharjo Hospital. There is an influence of brand experience on patient satisfaction with Panoramic X-Ray at Brawijaya Saharjo Hospital. There is an influence of brand awareness on patient satisfaction with Panoramic X-Ray at Brawijaya Saharjo Hospital. There is an effect of patient satisfaction on the quality of Panoramic X-Ray services at Brawijaya Saharjo Hospital. There is an influence of brand experience on service quality with Panoramic X-Ray patient satisfaction as a mediating variable at Brawijaya Saharjo Hospital, this means that if the brand experience improves, the quality of service will also experience a significant increase accompanied by an increase in patient satisfaction. There is an influence of brand awareness on service quality with Panoramic X-Ray patient satisfaction as a mediating variable at Brawijaya Saharjo Hospital, this means that if brand awareness increases, then the quality of service will also experience a significant increase accompanied by patient satisfaction. Keywords: Brand Experience, Brand Awareness, Patient Satisfaction, Service Quality